2014
DOI: 10.1002/cbin.10229
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation rate of stem cells derived from human dental pulp and identification of differentially expressed genes

Abstract: Stem cells from human exfoliated deciduous teeth (SHED) and dental pulp stem cells (DPSCs) obtained from the dental pulp of human extracted tooth were cultured and characterized to confirm that these were mesenchymal stem cells. The proliferation rate was assessed using AlamarBlue® cell assay. The differentially expressed genes in SHED and DPSCs were identified using the GeneFishing™ technique. The proliferation rate of SHED (P < 0.05) was significantly higher than DPSCs while SHED had a lower multiplication r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…This is probably due to the widespread use of FBS in published studies on DPSCs culture. 2,34 However, serum from animal source can present disadvantages such as risks of infections and immunological reactions. Indeed, mesenchymal stem cells have been reported to express N-glycolylneuraminic acid (Neu5Gc) xenoantigen that humans are unable to synthesize, indicating that cells uptake them from the culture media components.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the widespread use of FBS in published studies on DPSCs culture. 2,34 However, serum from animal source can present disadvantages such as risks of infections and immunological reactions. Indeed, mesenchymal stem cells have been reported to express N-glycolylneuraminic acid (Neu5Gc) xenoantigen that humans are unable to synthesize, indicating that cells uptake them from the culture media components.…”
Section: Discussionmentioning
confidence: 99%
“…Among the important advantages of dental MSCs compared to other SC sources, such as bone marrow and adipose tissues, are their higher proliferative capacity, facilitating ex vivo expansion in sufficient cell numbers [26, 27]; easy isolation by noninvasive routine clinical procedures (e.g., extraction of impacted third molars or premolars for orthodontic reasons); and the absence, as reported so far, of major adverse reactions, concerning, for example, teratoma formation following in vivo application [28]. Previous studies have shown that DPSCs have the ability to produce single-cell derived Colony Forming Units (CFUs), survive for longer periods without undergoing senescence, and exhibit higher (80–100 times) proliferation rates than BMMSCs [1].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there aren't any reports of cancer formation caused by transplantation of DPSCs, unlike cases of induced pluripotent stem cells or embryonic stem cells. Ethical considerations and immune‐compatibility problems usually faced with totipotent and pluripotent stem cells are absent with DPSCs since they are isolated from an easily accessible autologous source (Abdullah et al, ; Zhao, Wang, et al, ).…”
Section: Dpscsmentioning
confidence: 99%